Implementasi Kegiatan Mewarnai Menggunakan Media Kolase dalam Meningkatkan Kreativitas pada Anak Usia Dini di PAUD Nursyamsiani Tahun Ajaran 2023/2024 - Siti Maimunah; Akmal Walad Ahkas; Rina Devianty (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
The problem in this research is the lack of implementation process in coloring activities using collage media in increasing creativity in early childhood, the lack of implementation of collage media in increasing creativity in early childhood at PAUD Nursyamsiani, as well as limited teachers to support coloring activities in increasing creativity in early childhood at Nursyamsiani PAUD. The aim of this research is to describe the process of implementing coloring activities using collage media to increase creativity in early childhood at Nursyamsiani PAUD Bakaran Batu Village. This research uses qualitative research with a descriptive approach. The research subjects were school principals and teachers, as well as 25 children with specifications of 13 girls and 12 boys at early age at PAUD Nursyamsiani, complete documents for coloring activities using collage media in increasing creativity in early childhood including the implementation of coloring activities and teaching modules, implementation of coloring assessments, as well as teaching tools such as collage media. Data collection techniques use 3 methods, namely observation, interviews and documentation. Based on research conducted, coloring activities using collage media have a very important role in the development of creativity in early childhood.